Otoritas Keagamaan Di Era Digital: Pergeseran Peran Dai Dalam Media Sosial - Qusyaeri Aziz; Muhammad Rafli Farid Al Farisi; Taufan Azhari Mujahid; Ahmad Irfan; Siti Nuri Nurhaidah (Yayasan Syamil Quran Nunukan, 2026)
The rapid development of digital technology has brought significant changes to the landscape of Islamic da‘wah, particularly in terms of religious authority. Social media platforms such as YouTube, Instagram, and TikTok have become primary spaces for the dissemination of religious messages, enabling them to reach broad audiences beyond the boundaries of traditional institutional structures. This study aims to analyze the transformation of religious authority and the shifting role of da‘i (Islamic preachers) in the digital era. This research employs a qualitative approach using a library research method that examines a range of recent scholarly literature on digital da‘wah, religion and media, and Islamic communication. The findings indicate that religious authority has shifted from a knowledge-based and hierarchical model toward a more fluid, participatory model shaped by digital visibility and interaction. In this context, da‘i no longer function solely as transmitters of religious teachings but also as content creators and influencers who actively negotiate their authority within the digital public sphere. Although this transformation has expanded access to religious knowledge, it has also generated challenges, including the commodification of religion, the simplification of religious teachings, and the emergence of pseudo-authorities. This study contributes to a deeper understanding of the dynamics of da‘wah and the construction of religious authority in the digital age.